Short-term low-intensity Early Start Denver Model program implemented in regional hospitals in Northern Taiwan. (April 2023) - Chiang, Chung-Hsin; Lin, Tzu-Ling; Lin, Hsiang-Yuan; Ho, Suk Yin; Wong, Ching-Ching; Wu, Hsin-Chi
The Early Start Denver Model is an evidence-based, comprehensive naturalistic developmental behavioral intervention for young and very young children with autism spectrum disorder. This interdisciplinary model is suitable for the Taiwanese public health system. In this study, we evaluated the effectiveness of an Early Start Denver Model program with adaptation, including a lower intensity, shorter duration, and delivery in general hospitals by multidisciplinary professionals. A quasi-experimental study with pre-, post-intervention, and 6-month follow-up was conducted. Forty-five young children with autism spectrum disorder, aged 2–4 years, were grouped into the Early Start Denver Model and control (the usual community treatment) groups. The Early Start Denver Model group received 6 months of one-on-one intervention for approximately 8–9 h per week. Compared with the control group, the Early Start Denver Model group showed greater improvements in overall development quotient and nonverbal development quotient from pre- to post-intervention, but these differences (a Group-by-Time interaction) did not sustain at the 6-month follow-up. Being mindful of some potential threats to internal validity associated with clinical trial designs and implementation, this study provides preliminary evidence to support the effectiveness of the Early Start Denver Model intervention in regional general hospital settings in the context of Han-Chinese-mainly culture. Lay Abstract: The Early Start Denver Model is an evidence-based early intervention program for young and very young children with autism. This interdisciplinary model is used by many types of professionals, such as psychologists, occupational therapists, speech pathologists, early child special educators, and paraprofessionals, as well as by parents. Most previous studies on the Early Start Denver Model were conducted in the West, and there are scarce studies on the topics of generalization in culture and countries outside the Western world. In this study, we evaluated the effect of the Early Start Denver Model with some adaptations, including a lower intensity, shorter duration, and delivery in regional general hospitals in Northern Taiwan. In total, 45 young children with autism, aged 2–4 years, were divided into the Early Start Denver Model and community-based control groups. The children in the Early Start Denver Model group received one-on-one intervention for approximately 8–9 h per week for 6 months. The results revealed that compared with the control group, the Early Start Denver Model group showed greater gains in overall development ability and nonverbal development ability from pre- to post-intervention. However, these differences did not sustain at the 6-month follow-up after the completion of the intervention. Being mindful of some caveats in trial designs, this study provides preliminary evidence to support the effectiveness of the Early Start Denver Model intervention in the regional general hospital settings in the context of Han-Chinese-mainly culture. Our findings can provide helpful information to stakeholders and policymakers of early intervention service systems for children with autism in Taiwan, as well as in Asian countries.